The Serido Group of NE Brazil, a late Neoproterozoic pre- to syn-collisional basin in West Gondwana: insights from SHRIMP U-Pb detrital zircon ages and Sm-Nd crustal residence (T-DM) ages - Van Schmus, W. R.; Neves, BBD; Williams, I. S.; Hackspacher, P. C.; Fetter, A. H.; Dantas, E. L.; Babinski, M. (Elsevier B.V., 2003)
The Serido Group is a deformed and metamorphosed metasedimentary sequence that overlies early Paleoproterozoic to Archean basement of the Rio Grande do Norte domain in the Borborema Province of NE Brazil. The age of the Serido Group has been disputed over the past two decades, with preferred sedimentation ages being either Paleoproterozoic or Neoproterozoic. Most samples of the Serido Formation, the upper part of the Serido Group, have Sm-Nd T-DM ages between 1200 and 1600 Ma. Most samples of the Jucurutu Formation, the lower part of the Serido Group, have T-DM ages ranging from 1500 to 1600 Ma; some basal units have T-DM ages as old as 2600 Ma, reflecting proximal basement. Thus, based on Sm-Nd data, most, if not all, of the Serido Group was deposited after 1600 Ma and upper parts must be younger than 1200 Ma.Cathodoluminescence photos of detrital zircons show very small to no overgrowths produced during ca. 600 Ma Brasiliano deformation and metamorphism, so that SHRIMP and isotope dilution U-Pb ages must represent crystallization ages of the detrital zircons. Zircons from meta-arkose near the base of the Jucurutu Formation yield two groups of ages: ca. 2200 Ma and ca. 1800 Ma. In contrast, zircons from a metasedimentary gneiss higher in the Jucurutu Formation yield much younger ages, with clusters at ca. 1000 Ma and ca. 650 Ma. Zircons from metasedimentary and metatuffaceous units in the Serido Formation also yield ages primarily between 1000 and 650 Ma, with clusters at 950-1000, 800, 750, and 650 Ma. Thus, most, if not all, of the Serido Group must be younger than 650 Ma. Because these units were deformed and metamorphosed in the ca. 600 Ma Brasiliano fold belt during assembly of West Gondwana, deposition probably occurred ca. 610-650 Ma, soon after crystallization of the youngest population of zircons and before or during the onset of Brasiliano deformation.The Serido Group was deposited upon Paleoproterozoic basement in a basin receiving detritus from a variety of sources. The Jucurutu Formation includes some basal volcanic rocks and initially received detritus from proximal 2.2-2.0 Ga (Transamazonian) to late Paleoproterozoic (1.8-1.7 Ga) basement. Provenance for the upper Jucurutu Formation and all of the Serido Formation was dominated by more distal and younger sources ranging in age from 1000 to 650 Ma. We suggest that the Serido basin may have developed as the result of late Neoproterozoic extension of a pre-existing continental basement, with formation of small marine basins that were largely floored by cratonic basement (subjacent oceanic crust has not yet been found). Immature sediment was initially derived from surrounding land; as the basin evolved much of the detritus probably came from highlands to the south (present coordinates). Alternatively, if the Patos shear zone is a major terrane boundary, the basin may have formed as an early collisional foredeep associated with south-dipping subduction. In any case, within 30 million years the region was compressed, deformed, and metamorphosed during final assembly of West Gondwana and formation of the Brasiliano-Pan African fold belts. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Serido Group; Neoproterozoic; detrital zircons; geochronology; Brazil; Borborema Province